(untitled) (The Research of Medical Science Review, 2025)
Objective: The objective of the study was to assess thyroid function tests in patients hospitalized with COVID-19 and examine how these results influenced the progression of the disease. Study Design: This cross-sectional study was conducted between 2022 and 2023 in Larkana, Sindh, Pakistan. It involved 129 COVID-19-positive patients who were hospitalized in the COVID-19 ward and treated at private clinics. Methodology: T3, T4, and TSH thyroid function tests, together with other initial investigations, were performed on Covid-19 patients. Patients with prior thyroid-related conditions were disqualified, as were those with unreported prior outcomes. Vaccination status was confirmed by collecting the vaccine card. The data was analysed using SPSS version 26. Results: A study of 129 individuals found that 51% experienced tiredness, depression, constipation, and muscle soreness. Gender differences were observed in weight distribution, with males having a higher proportion of normal weight and overweight individuals. Thyroid-related indicators showed varied distributions, highlighting significant changes in thyroid function. Conclusion: This study concluded that the thyroid function can be disrupted in all patient groups during a COVID-19 infection, even in individuals without pre-existing thyroid issues. This preliminary study suggests that changes in blood levels of T3, T4, and TSH could serve as important indicators of COVID-19 pneumonia